Association of Family History With Cardiovascular Disease in Hypertensive Individuals in a Multiethnic Population. Issue 12 (December 2016) - Valerio, Luca; Peters, Ron J.; Zwinderman, Aeilko H.; Pinto‐Sietsma, Sara‐Joan
Abstract : Background: Hypertension alone is a poor predictor of the individual risk of cardiovascular disease. Hereditary factors of which hypertension is merely a marker may explain why some hypertensive individuals appear more susceptible to cardiovascular disease, and why some ethnicities have more often seemingly hypertension‐related cardiovascular disease than others. We hypothesize that, in hypertensive individuals, a positive family history of cardiovascular disease identifies a high‐risk subpopulation. Methods and Results: Healthy Life in Urban Settings (HELIUS) is a cohort study among participants of Dutch, South‐Asian Surinamese, African Surinamese, Ghanaian, Turkish, and Moroccan origin aged 70 years and younger. In participants with hypertension (n=6467), we used logistic regression to assess the association of family history of cardiovascular disease with prevalent stroke and nonstroke cardiovascular disease, adjusting for sex, age, education, and smoking. To detect ethnic differences, we tested for interaction between family history and ethnicity and stratified the analysis by ethnicity. A positive family history was associated with a higher prevalence of nonstroke cardiovascular disease (odds ratio [OR], 2.05; 95% CI, 1.65–2.54) and stroke (OR, 1.62; 95% CI, 1.19–2.20). The strongest association of family history with nonstroke cardiovascular disease was found among the Dutch (OR, 2.47; 95% CI, 1.37–4.44) and with stroke among the African Surinamese (OR, 2.17; 95% CI, 1.32–3.57). The interaction between family history and African Surinamese origin for stroke was statistically significant. Conclusions: In multiethnic populations of hypertensive patients, a positive family history of cardiovascular disease may be used clinically to identify individuals at high risk for nonstroke cardiovascular disease regardless of ethnic origin and African Surinamese individuals at high risk for stroke.